Mycobacteriosis of productive animals in the conditions of dairy farms - Panivska, Olha V.; Shevchuk, Viktor M. (My University, 2024)
The growing incidence of mycobacteriosis in people - infectious diseases caused by non-tuberculous mycobacteria - is an urgent problem in human medicine. Mycobacteriosis of animals in most countries is in the field of close attention of veterinary medicine scientists. In Ukraine, the number of farms where productive animals with para allergic reactions to tuberculin are found is constantly increasing, which complicates the diagnosis of tuberculosis. Therefore, the study of the nature of these allergic reactions becomes one of the most urgent questions of veterinary science. Along with this, in dairy cattle breeding, this problem concerns not only the diagnosis of tuberculosis but also the economic sphere, as it often leads to the forced slaughter of young animals and highly productive cows. On the other hand, identifying several non-tuberculous mycobacteria species in human mycobacteriosis patients, which are involved in sensitizing the body of cows, gives the problem of animal mycobacteriosis prevention a medical and social significance. All of the above was the basis for establishing the reasons for the permanent selection of cows reacting to tuberculin in one of the dairy farms of the Volyn region, which has always been safe from tuberculosis. A comprehensive study using epizootological analysis and clinical, patho-anatomical, histological, bacteriological, and statistical research methods was carried out from 2018 to 2023. The conducted studies established that an epizootic process caused by infection of animals with nontuberculosis is functioning among the cattle of a dairy farm mycobacteria. Mycobacterium scrofulaceum, M. fortuitum, and Nocardia spp, which were isolated and identified from the lymph nodes, lymphoid tissue of the submucosal layer of the large intestine of infected animals, cause significant histological and pathoanatomical changes, which indicates the presence of a clinically hidden infectious process, which is accompanied by sensitization of the animal organism. Epizootological analysis of the results of allergic studies using a simultaneous sample, as well as multiple bacteriological studies of biomaterial from animals that reacted positively to PPD-tuberculin and an allergen of atypical mycobacteria, established that allergic reactions to tuberculin had a para allergic nature and reflected the presence of an infectious process in the animal's body.
Keywords: tuberculosis; tuberculin; allergen of atypical mycobacteria; epizootic process; infectious process; allergic reactions; diagnosis